2003
DOI: 10.1021/la026601g
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Polymorphism of the Palmitic Acid/Cholesterol System by the pH

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
87
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 55 publications
(138 reference statements)
18
87
1
Order By: Relevance
“…A similar phase separation probably occurs in the state ␣ of our systems. The repeat distance of the L-phase agrees with D-values obtained for a palmitic acid/CHOL system at high pH as described by Quimet et al [45]. These authors even showed that with increasing CHOL concentration in the palmitic acid/CHOL system, the lamellar repeat distance slightly increases.…”
Section: Evaluation Methodssupporting
confidence: 89%
“…A similar phase separation probably occurs in the state ␣ of our systems. The repeat distance of the L-phase agrees with D-values obtained for a palmitic acid/CHOL system at high pH as described by Quimet et al [45]. These authors even showed that with increasing CHOL concentration in the palmitic acid/CHOL system, the lamellar repeat distance slightly increases.…”
Section: Evaluation Methodssupporting
confidence: 89%
“…Moreover, there is still a strong debate dealing with the deprotonation state of the fatty acid in such mixtures. This has been noted in catanionic systems [20] but also in mixtures with alcohols [13,21,22]. In the stock solution of our microtubes, the pH is around 9.8 but we expect that both carboxylate and carboxylic groups coexist, although the concentration of COO À is probably higher since the pH is basic.…”
Section: Effect Of Phsupporting
confidence: 54%
“…However, the ratio [COO À ]/[COOH] is difficult to estimate since the pK a of a fatty acid varies with experimental conditions. Indeed, the pK a of fatty acids are expected to be below 7 but it was shown to be close to 8 for cholesterol-palmitic acid systems [21,23].…”
Section: Effect Of Phmentioning
confidence: 99%
“…reports. 27,41 The widths of these spectra were found to be very similar to those observed at pH 8.4 The measured diffusion coefficient in these conditions was 2.0 × 10 -11 m 2 /s, a value corresponding to that reported for PEG2000-PE micelles. 42 When PEG-Chol proportion in a mix with PA and cholesterol was between 1 and 20%, PEG diffusion coefficients were relatively constant and corresponded to about 2.4 × 10 -12 m 2 /s.…”
Section: Luvs Characterization the Hydrodynamic Diameters Of The Luvsupporting
confidence: 77%
“…41 The protonation state of the carboxylic group dictates the bilayer stability through its modulation of the lipid mixing properties and the bilayer interface hydration. At lower pH, PA head group is protonated, favoring phase separation from cholesterol and reducing the hydration of the bilayer interface; as a consequence, the destabilization of the fluid lamellar phase is observed.…”
Section: Dox Active Loading and Releasementioning
confidence: 99%